2011
DOI: 10.1123/jsm.25.5.391
|View full text |Cite
|
Sign up to set email alerts
|

More Than Motivation: Reconsidering Volunteer Management Tools

Abstract: Volunteers provide an essential human resource to sport organizations. Yet measures of motivation and satisfaction have had limited impact on an organization’s ability to improve their volunteer systems. This study applied the Kano Method to categorize volunteers’ perceptions of their experience into four dimensions of satisfaction: Attractive (or Satisfiers), Must-Be’s (or Dissatisfiers), One-Dimensional, and Indifferent. Four types of volunteers (44 sport continuous, 47 sport episodic, 49 nonsport continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 53 publications
3
50
0
3
Order By: Relevance
“…Yet, despite its broad application to many various volunteer contexts, recent subsequent research has reported that all of the VFI dimensions were not necessarily appropriate and some did not fit well when applied to specific volunteer groups involving seniors, young people, religious organizations and sports supporters [26,31]. This situation has been commonly proven in many volunteer studies that identified slightly different motivations from the VFI dimensions based upon volunteer characteristics and activities (see Table 1).…”
Section: Volunteer Motivationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Yet, despite its broad application to many various volunteer contexts, recent subsequent research has reported that all of the VFI dimensions were not necessarily appropriate and some did not fit well when applied to specific volunteer groups involving seniors, young people, religious organizations and sports supporters [26,31]. This situation has been commonly proven in many volunteer studies that identified slightly different motivations from the VFI dimensions based upon volunteer characteristics and activities (see Table 1).…”
Section: Volunteer Motivationsmentioning
confidence: 91%
“…Frank, Finnegan and Taylor (2004) asserted that volunteer motivation and satisfaction significantly influence volunteer retention. Subsequent volunteer studies have demonstrated that an individual's motivations for volunteering could vary according to their socio-demographics, social relationships and volunteer activities [6,26]. Therefore, the most prevalent view of the existing literature is that volunteer motivations represent multi-dimensional aspects of individuals.…”
Section: Volunteer Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação aos eventos esportivos de larga escala, o trabalho voluntário representa um núcleo fundamental na prestação de diferentes serviços e é considerado essencial para sua viabilidade e sucesso (BLANC, 1999;CUSKELLY et al, 2006;GIANNOULAKIS et al, 2008 (WARNER et al, 2011).…”
Section: Trabalho Voluntário Em Magaeventos Esportivosunclassified
“…Além disso, como o levantamento de informações foi, majoritariamente, conduzido em grupos, a predominância de relatos positivos pode, de certa forma, ter inibido a exposição de opiniões mais críticas. Outra limitação deve-se ao fato de a pesquisa ter acontecido cinco anos após a realização do Pan, o que pode ter influenciado a memória dos entrevistados e gerado perda de elementos importantes, especialmente negativos (WARNER et al, 2011).…”
Section: Considerações Finaisunclassified